Lateralization study of the basal ganglia, thalamus and supplying arteries in healthy individuals based on structure and connectivity analysis using 7.0T MRI - Hongqin Liang; Yawei Gu; Xiaoqi Yi; Li Kong; Jian Wang; Fajin Lv (NeuroImage)
The human cerebral cortex is known for its hemispheric specialization, which underpins a variety of functions and activities. However, it is not well understood if similar lateralization exists within the deep gray matter nuclei, such as the basal ganglia (BG) and thalamus, and their associated arteries, including the lenticulostriate arteries (LSAs). To explore this, we analyzed images from 7T MRI scans of 40 healthy young individuals. We isolated the LSAs and analyzed their morphological characteristics. Additionally, we segmented the bilateral BG and thalami into 28 subregions based on the Brainnetome atlas and calculated their volumes using single-subject voxel-based morphometry (VBM) analysis. We also obtained four parameters from Diffusion Tensor Imaging (DTI) within these 28 subregions. Bilateral comparisons were conducted using paired t-tests for all measurements. Connectivity-network matrices, based on the number of connecting fibers and fractional anisotropy between subregions, were constructed. The results showed that in the right-handed dominant population, we observed that the total number and length of LSAs in the left hemisphere exceeded those in the right. Among the 28 subregions, several showed leftward volume dominance, including the ventral caudate, globus pallidus, ventromedial putamen, medial pre-frontal thalamus, occipital thalamus, and caudal temporal thalamus. In contrast, the nucleus accumbens, dorsal caudate, dorsolateral putamen, pre-motor thalamus, sensory thalamus, posterior parietal thalamus, and lateral pre-frontal thalamus showed rightward volume dominance. Except for the ventral medial putamen (vmPu), all other subnuclei displayed at least three DTI measures with left-right differences. The connectivity between subregions revealed distinct patterns in the bilateral hemispheres, with a leftward dominance. Collectively, these findings enhance our understanding of lateralization within subcortical structures.